Exploring employee well-being among precarious (fixed-term) call center workers - Kortman, Carmalita (Organisational Psychology, 2023)
Organisations have readily adopted alternative forms of work that deviate from the traditional standard employment relationship. Temporary employment or fixed-term employment has become a norm, especially in the call centre industry. In addition to the call centre environment being a major contributor to stress and job insecurity, the status of temporary employment brings along its own damaging outcomes for those employees impacted. That is, the experiences of working in a call centre environment are enhanced by the experiences of being in a precarious employment relationship. The objective of this study was to investigate the well-being experiences of fixed-term contract call centre employees in a financial services sector institution. This qualitative study was conducted in the interpretive paradigm and utilised an exploratory descriptive approach to understand the phenomena under study. Nine (9) fixed-term employees from three (3) different servicing call centres in the business were interviewed telephonically for this study. The study sample comprised Black, Coloured, and Indian males and females with an average age of 25 years old, an NQF4 level education or higher, and average tenure of 2.5 years in the organisation. The findings indicated that fixed-term call centre employees perceived their work arrangements and environments to be sources of stress, insecurity and instability, a hindrance to career development, and expressed overall negative affect on their well-being. Employees' negative well-being experiences were intensified during the COVID19 lockdown period which brought about many consequences for the general economy and specifically those already in vulnerable work arrangements. The study found that social support amongst co-workers was a buffer between the pressures experienced by fixed-term call centre employees and their well-being.